Analysis Of Core Supply Chain Process Performance Based On The Lean Six Sigma Supply Chain Management Approach (Case Study: PT Pg. Candi Baru) - Krisna Ramadhian Arifano; Dira Ernawati; Sinta Dewi (Green Publisher Indonesia, 2024)
The aim of the research is to integrate the lean six sigma supply chain management concept to design and measure performance measurement models and determine the causes of company performance failures and then provide recommendations for improvement according to the lean concept. This research was carried out only up to the improvement stage. The result of this research is an overall performance measurement of 66.6666 where this value can be categorized as